Opportunities for Thai Investors in Sri Lanka - Premsrirut, Tassuree (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
The aim of this paper is to provide an in-depth analysis of investment opportunities, approaches, strategies, and incentives for Thai investors who would like to trade and invest in Sri Lanka. Sri Lanka not only has the potential of a highly accelerating economic growth, it also has a long-term mutual relationship with Thailand, and Sri Lanka is attracting more foreign direct investment. Sri Lanka has currently established a Board of Investment as the central facilitation point, and to provide incentives for investors. Numerous opportunities are awaiting Thai investors in many sectors, especially fishery, construction and property development, hotels and other accommodation, and tourism and hospitality. All of which is supported and promoted by Sri Lanka’s government. Investment strategies in Sri Lanka for Thai investors consist of 4 items: fund raising, workforce, tax exemption and location, in order to acquire the best incentives from the country.